Pengaruh Perubahan Posisi terhadap Hasil Ukur Tekanan Vena Sentral pada Pasien Critical Care di Gedung A RSUPN Dr. Cipto Mangunkusumo - Julham Mubarak; Erika Lubis; Nani Asna Dewi (Jurnal Ilmu Kesehatan Dharmas Indonesia, 2021)
Many factors would affect the accuracy of Central Venous Pressure (CVP) measurement such as patient’s position during the measuring. Any fault that occurs while measuring could bring a fatal impact such as death. This study aimed to determine the effect of the CVP measuring position towards the results CVP  measurement of critical care patients. This study is a quasi-experimental study with Pre and Post Test design without control by measuring the CVP of 45 respondents with supine and semi-fowler positions. Statistical test using paired samples T-test. The results showed a significant difference in the results of measuring CVP in critical care patients between before and after changing positions with p-value = 0.003. In conclusion, this study indicates that there are differences in the results of the CVP measurement position and it is hoped that nurses can take measurements correctly to avoid any intervention error throughout providing patient care.